Developing Undergraduates' Multicultural Skills for Career Success and National Integration - Chong, Yen Wan; Rahman, Maria Abdul (International Review of Management and Marketing, 2016)
In today's global work environment characterised by workplace diversity, multicultural skills or cultural intelligence (CQ) are essential soft skills for managerial success. In a multi-cultural country like Malaysia, the development of multicultural sensitivity is also important so that its citizens will learn to live in harmony. This paper reports on a study which reviews the effectiveness of a campus wide program that was implemented by a Malaysian public university which specializes in management education from 2011 to 2013 that aimed to facilitate the development of multicultural skills in undergraduates. This study has provided some insights on areas for improvement of future programs. The findings of the study also indicated that there is a need to promote higher interaction between the university's local and international students. One of the best ways to develop multi-cultural skills among Malaysian undergraduates is to promote greater interactions between Malaysian and non-Malaysian students as well interactions between Malaysian students of various races in campus. Keywords: Graduate Employability Skills, Cultural Intelligence, Management Education JEL Classifications: J61, M16, I25